Pandemic and humanized care in a Psychosocial Care Center in Recife - Sá, Camila Maria de; Cotrim, Geiziane Silva (Argumentum, 2024)
This work analyses the characteristics of humanised care, based on the National Humanisation Policy (PNH), in a Psychosocial Care Centre (CAPS) in Recife in view of the COVID-19 pandemic. Data collection was conducted through semi-structured interviews with four participants linked to the CAPS. The results highlight challenges, on a territorial basis, in the execution of the fundamental precepts for voluntary psychological care aimed at those with mental disorders and/or psychological distress, because of the mandated social distancing, placed upon an already extremely fragile and sometimes dysfunctional intersectoral network. Deviation from a medical-centred care perspective is confirmed, with compromises being made in many of the guidelines recommended by the PNH norms.